Water Infiltration and Evaporation Process with ATP Addition in Newly Reclaimed Soil - Linjie Kong; Xiaoman Fan; Xinyue Li; Biyu Zhai; Zhangjie Tian; Yangkai Hong; Pengbo Jiang; Jiaxin Zhang; Juan Wang (Agronomy)
The newly reclaimed soil is an important reserve land resource, while it faces challenges such as poor water retention and low fertility. Therefore, it requires improvement through the use of soil amendments. Attapulgite (ATP) is abundant in northwest China with excellent properties and can be used as an amendment for newly reclaimed soil. The effects of ATP and its addition rate on infiltration and evaporation characteristics in newly reclaimed soil were studied by experiments and model simulation. Three addition gradients (2%, 4%, and 6%) were set in this study, and no ATP addition was used as a control (CK). The results show that ATP treatment prolonged the infiltration duration, reduced the wetting front migration distance, and reduced the accumulated evaporation. Both the Philip model and the Kostiakov model can accurately describe the infiltration process of newly reclaimed soil with ATP addition; the soil evaporation process can be fitted well with the Rose model. In this study, ATP addition affected both sorptivity and the stable infiltration rate of the reclaimed soil. During the evaporation, the soil evaporation effect was inversely proportional to the addition rates of ATP, and the ATP addition rate at 2% had the best effect on reducing soil evaporation. In summary, the ATP addition was beneficial top soil infiltration and evaporation, thus improving the poor water retention of newly reclaimed land and is a reasonable choice for efficient construction of new reclaimed land.